Critical Incidents und der Faktor „Kulturalität“ in der grenzüberschreitenden Wirtschaftskommunikation - Kiefer, Karl-Hubert (Glottodidactica, 2015)
Exemplified by electronic correspondence between polish tax advisers and german clients the article deals with the question what kind of determinants in professional cross-border business communication must be met in order to give "culture" a meaning, so that we can speak of „critical incidents“.